The archaeology of Anatolia. recent discoveries (2017-2018) - Steadman, Sharon R.; McMahon, Gregory (Cambridge Scholars Publishing, 2019)
This third volume in the Archaeology of Anatolia series offers reports on the most recent discoveries from across the Anatolian peninsula. Periods covered here span the Epipalaeolithic to the Medieval, and sites and regions range from the western Anatolian coast to Van, as well as the southeast. The contributors offer nearly real-time updates on their ongoing excavations and surveys across the Anatolian landscape. A new section in this third volume, ""The State of the Field,"" presents the latest findings in critical areas of Anatolian archaeology. The Archaeology of Anatolia series represents.